The impact of social technologies on student performance in a collaborative learning environment. (26th June 2007) - Deeb, Khaled Kevin
Research has shown that effective learning is attributed to the interaction of people with different experiences, knowledge and skills. Learning can also be maximised within a social setting that facilitates formal and informal interactions. However, this learning environment calls for incentives, a structured format for collaboration, and the support of an integrated set of interactive learning tools and resources. This research presents the design structure of an integrated IT senior capstone course that engages students in web-blended learning activities. Results support significant improvement in academic performance and advancement in the collective and intuitive knowledge of students at both the social and technical levels.